RUPTURE DIMENSIONS AND RUPTURE PROCESSES OF FLUID-INDUCED MICROCRACKS IN SALT ROCK - Dahm T. (My University, 2001)
We developed and applied a simple empirical Green function method to study induced microcracks observed during hydraulic fracturing experiments in salt rock. Either unidirectional ruptures on rectangular faults or allround ruptures on elliptical faults are tested to explain the observed directivity effects in body-wave amplitude spectra. Mostly, the rectangular rupture model and horizontal fault planes are favored. The average rupture lengths are between 15 and 27mm, the average rupture durations between 14 and 26μs. Small average rupture velocities of 30% of the S-wave velocity of the rock are indicated. The dispersive low-frequency coda-waves present in the data look similar to coda-waves observed during other hydraulic fracturing experiments and to long-period events from some volcanoes, which have been explained by the resonance of a fluid-filled crack. The radiation pattern of first motion amplitudes of most events is dominated by a dip-slip double-couple indicating slip on horizontal or vertical planes. We cannot distinguish whether the observed low-frequency coda-waves are influenced by a source effect or by a possible sensor-borehole coupling. However, a simple method using Gauss filter at different center frequencies and relocation is tested to analyze the low-frequency coda-waves in terms of source models.
Keywords: HYDRAULIC FRACTURING; HYBRID EVENTS; FLUID-INDUCED SEISMICITY; EMPIRICAL GREEN FUNCTIONS